Behavioral Impulsivity and Risk‐Taking Trajectories Across Early Adolescence in Youths With and Without Family Histories of Alcohol and Other Drug Use Disorders. (14th July 2015) - Dougherty, Donald M.; Lake, Sarah L.; Mathias, Charles W.; Ryan, Stacy R.; Bray, Bethany C.; Charles, Nora E.; Acheson, Ashley
<x xml:space="preserve">Abstract</x> Background Youths with family histories of alcohol and other drug use disorders (FH+) are at increased susceptibility for developing substance use disorders relative to those without such histories (FH−). This vulnerability may be related to impaired adolescent development of impulse control and elevated risk‐taking. However, no previous studies have prospectively examined impulse control and risk‐taking in FH+ youth across adolescence. Methods A total of 386 pre‐adolescents (305 FH+, 81 FH−; aged 10 to 12) with no histories of regular alcohol or other drug use were compared on behavioral measures of impulsivity including delay discounting, response initiation (Immediate Memory Task), response inhibition impulsivity (GoStop Impulsivity Paradigm), and risk‐taking (Balloon Analogue Risk Task‐Youth). Youths completed these laboratory tasks every 6 months, allowing for the examination of 10‐ to 15‐year‐olds. Hierarchical linear modeling was used to characterize the development of impulse control and risk‐taking as shown in performance of these tasks throughout adolescence. Results We found that (i) FH+ youths had increased levels of delay discounting and response inhibition impulsivity at study entry; (ii) regardless of FH status, all youths had relatively stable delay discounting across time, improvements in response inhibition and response initiation impulsivity, and increased risk‐taking; and (iii) although FH+ youths had increased response inhibition impulsivity at pre‐adolescence, these differences were negligible by mid‐adolescence. Conclusions Heightened delay discounting in FH+ pre‐adolescents coupled with normal adolescent increases in risk‐taking may contribute to their increased susceptibility toward problem substance use in adolescence.